Memahami Orang Lain melalui Keterampilan Mendengar secara Empatik - Makmun, Sukron (Bina Nusantara University, 2013)
This paper discusses how to develop empathic listening skill to understand others. The purposes of writing this paper are: exploring of the concept of empathic listening and its urgency in the communication process, describing the barriers that are often experienced by a person to listen in the communication process, and describing how to develop empathic listening skills. In this paper the author uses descriptive-analytical method. The procedures are: 1) data collection, 2) classification of data, 3) data analysis, and 4) drawing conclusions. Source of the data was gained from information available in the literatures. The data analysis was done by using content analysis method (content analysis), which is an attempt to explore the symbolic meaning of the message or the contents of a book or other writings products. The results showed that one of the skills currently needed by humans and often escaped the attention is empathic listening skill. It can be said that the failure in communication may be caused by lack of adequate skills in this regard. Therefore, by developing the skill of empathic listening communication failure can be ravealed, misunderstandings can be avoided and disputes can be eliminated.